Ni(Pt)-based CMOS-compatible contacts on p-InGaAs for III–V photonic devices. (February 2023) - Boyer, Flore; Dabertrand, Karen; Bernier, Nicolas; Jany, Christophe; Gergaud, Patrice; Grégoire, Magali; Rafhay, Quentin; Rodriguez, Philippe
Abstract: Nickel-based contacts are envisioned for the integration of III–V devices (such as emitters and detectors) on a 300 mm platform. We have thus investigated the structural, morphological and electrical properties of Ni/p-In0.53 Ga0.47 As and Ni0.9 Pt0.1 /p-In0.53 Ga0.47 As systems. The phase sequence obtained for the Ni/InGaAs system was consistent with the existing literature. In the as-deposited state and at low temperature, an intermixed and amorphous layer of a-Ni x InGaAs was formed. At 250 ℃, the Ni3 InGaAs phase grew. This phase was stable up to 350 ℃. Then, an evolution of its stoichiometry was observed. At 400 ℃, the NiAs phase started to grow. The analysis of element distribution suggested that, at higher temperature, a Ni x Ga y phase was formed, most likely γ -Ni3 Ga2 . The morphology of this system stayed relatively smooth over the whole studied range of temperature, yielding a high stability of the electrical properties. The addition of Pt in the system made solid-state reactions more complicated. It had an impact on the Ni3 InGaAs phase stoichiometry and led to the formation of Pt x In y compounds, namely Pt3 In7 and PtIn2 . At high temperature, the presence of these compounds impacted the system morphology and, consequently, electrical properties.